1985
DOI: 10.1111/j.1365-2184.1985.tb00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemopoietic modulation in tumour‐bearing animals: enhanced progenitor‐cell production in femoral marrow

Abstract: Altered haematopoiesis in the femoral marrow was observed in mice bearing the Lewis lung carcinoma (LLca). During tumour growth, a marked reduction was observed in the myeloperoxidase-positive cells (granulocytes) of the marrow 7 days after inoculation of the LLca tumour reaching a nadir (17% of control) by day 28. Accompanying this suppression of mature white cells was a gradual expansion of the CFU,-GM compartment followed by an increase in the number of femoral CFU,. Humoral-stimulating activity (HSA) incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…When analyzing the results, we should remember that the test we used to assess the level of 3H-thymidine incorporation by BM cells is suitable for a comparative assessment of the level of BM cell proliferation and suppressor activity under specific conditions, but that it cannot be used for adequate assessment of colony-stimulating activity [8]. The colony-stimulating capacity of tumor supematants was tested by the ability to stimulate the growth of BM colonies in methyl cellulose.…”
Section: Resultsmentioning
confidence: 99%
“…When analyzing the results, we should remember that the test we used to assess the level of 3H-thymidine incorporation by BM cells is suitable for a comparative assessment of the level of BM cell proliferation and suppressor activity under specific conditions, but that it cannot be used for adequate assessment of colony-stimulating activity [8]. The colony-stimulating capacity of tumor supematants was tested by the ability to stimulate the growth of BM colonies in methyl cellulose.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have examined hematopoietic changes in tumor-bearing animals, including myeloid progenitors (Balducci and Hardy 1983; Kovacs et al 1985;Young et al 1987), and have generally shown that tumor growth is associated with an initial increase in bone marrow hematopoiesis, followed by suppression as the neoplastic process progresses. This expansion in the number of progenitor cells early in carcinogenesis may be due to production of colony stimulating factor from the tumor (Ikeda et al 1985) or enhanced migration of bone-marrow derived leukocytes to the tumor site (Balducci and Hardy 1983).…”
Section: Discussionmentioning
confidence: 99%